2014
DOI: 10.1177/2151458514542336
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Impact of Indirect Markers of Renal Function in Elderly Patients With Hip Fracture

Abstract: Introduction: There are risk factors associated with mortality in patients older than 70 years with hip fracture, including kidney function. However, indirect formulas to calculate glomerular filtration rate are not validated in patients older than 70 years. We analyzed whether the formula hematocrit, urea, and gender (HUGE) can be used as a prognostic factor. Material and Methods: A retrospective cohort study of 88 patients older than 70 years with a diagnosis of hip fracture. At admission, clinical and bioch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
(38 reference statements)
1
4
0
Order By: Relevance
“…Te observation that more severe CKD stage was associated with a higher risk of mortality is in line with most published reports [13,26,28,60,61,[65][66][67][68][69][70][71][72][73][74] on 30-day and 1year mortality; a signifcantly higher LOS in HF patients with CKD was also reported [75]. Some authors, however, observed an increase of all-cause mortality only in patients with CKD stage G4 (but not with stages G3a, G3b, G5, G3-G5) [76] or stage G5 [75,77], in one study of HF patients (>65years of age) no signifcant association was observed between higher stages of impaired renal function and mortality [29], and in another study severity of CKD did not afect 1-year mortality rate and medical complications in patients with intertrochanteric fracture [77].…”
Section: Ckd and Hospital Outcomessupporting
confidence: 90%
“…Te observation that more severe CKD stage was associated with a higher risk of mortality is in line with most published reports [13,26,28,60,61,[65][66][67][68][69][70][71][72][73][74] on 30-day and 1year mortality; a signifcantly higher LOS in HF patients with CKD was also reported [75]. Some authors, however, observed an increase of all-cause mortality only in patients with CKD stage G4 (but not with stages G3a, G3b, G5, G3-G5) [76] or stage G5 [75,77], in one study of HF patients (>65years of age) no signifcant association was observed between higher stages of impaired renal function and mortality [29], and in another study severity of CKD did not afect 1-year mortality rate and medical complications in patients with intertrochanteric fracture [77].…”
Section: Ckd and Hospital Outcomessupporting
confidence: 90%
“… 29 - 31 Lastly, a study, based on a population of 88 over-70 patients, evidenced that the HUGE (Hematocrit, Urea, GEnder) equation was an independent risk factor for mortality while no statistical correlation was found with eGFR calculated with Cockcroft-Gault, MDRD or CKD-EPI equations. 32 The only recent meta-analysis on the subject reported a moderate evidence in CKD as a mortality risk factor in a population over 60 years of age. 33 Therefore, it remains doubtful whether CKD can be considered a risk factor in determining an increased mortality in this population of patients.…”
Section: Discussionmentioning
confidence: 99%
“…In that study, eGFR CDK-EPI was not significantly associated with mortality in a follow-up period of three years [9]. However, the analysis was performed on only 88 patients and was not adjusted for the welldocumented predictors of mortality of hip fracture patients.…”
Section: Baselinementioning
confidence: 91%
“…Publications on using eGFR CDK-EPI as a marker of renal function to predict mortality in hip fracture patients are almost non-existent. In one study with a small population and limited methodology, eGFR CDK-EPI was not significantly associated with mortality [9].…”
Section: Introductionmentioning
confidence: 96%